2012
DOI: 10.1542/peds.2012-1516
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity–Related Outcomes After Human Papillomavirus Vaccination of 11- to 12-Year-Olds

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Concerns persist about sexual disinhibition after human papillomavirus (HPV) vaccination of preteenage girls. Self-reported surveys have indicated few anticipated behavior changes after HPV vaccination. Little is known about sexual activity-related clinical outcomes after HPV vaccination. WHAT THIS STUDY ADDS:Utilizing managed care organization electronic data, we evaluated the incidence of adverse outcomes of sexual activity among vaccinated preteenage girls and found little diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
108
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(128 citation statements)
references
References 25 publications
18
108
0
2
Order By: Relevance
“…Both answers reflect a more responsible attitude to sex and indicate that the motive to be vaccinated was not promiscuity but rather an act of caution. Bednarczyk et al [29] have shown that vaccinated girls 11-12 have not any increased risk of pregnancy, STD or contraceptive counselling a finding that is supported by other studies [30]. In our study the vaccinated population started sex earlier after having discussed it with their mothers and doctors significantly more common than non-vaccinated.…”
Section: Discussionsupporting
confidence: 88%
“…Both answers reflect a more responsible attitude to sex and indicate that the motive to be vaccinated was not promiscuity but rather an act of caution. Bednarczyk et al [29] have shown that vaccinated girls 11-12 have not any increased risk of pregnancy, STD or contraceptive counselling a finding that is supported by other studies [30]. In our study the vaccinated population started sex earlier after having discussed it with their mothers and doctors significantly more common than non-vaccinated.…”
Section: Discussionsupporting
confidence: 88%
“…49 Reassuring parents that the vaccine is safe and that there is no evidence that HPV vaccine increases sexual activity may dispel their concerns. 50 Some parents are concerned primarily about the pain associated with immunizations. Strategies to reduce pain include administering vaccines quickly without aspirating, holding the child upright, administering the most painful vaccine last, and e5…”
Section: Parents' Varied Concerns About Vaccines Should Be Addressedmentioning
confidence: 99%
“…This found no clinically meaningful difference between the vaccine exposed group compared to the vaccine unexposed group [13]. Liddon et al also examined this issue in a nationally representative survey and found no association between receipt of the HPV vaccine and being sexually active or having more sexual partners [14].…”
mentioning
confidence: 98%